Utilization of Blockchain Technology for Management E-Certificate Open Journal System - Agustin, Farida; Aini, Qurotul; Khoirunisa, Alfiah; Nabila, Efa Ayu (APTISI Transactions on Management (ATM), 2020)
The application of blockchain technology in e-certificates in the open journal system is needed to validate and distribute managed e-certificates in each journal issue. With tools in the form of conceptualized and managed blockcerts allows users to use and verify the authenticity of e-certificates that are closely linked to the blockchain. Observation on the open journal system and applied blockchain tools in the form of blockcerts as a place to issue e-certificates with guaranteed security so that e-certificates are verified as well as managed data. Issuance of e-certificates is still considered unsafe because it can be easily forged. Specifically, this study produced two benefits, namely: (1) Issuance of e-certificates in an open journal system is more verified, data is managed and there will not be duplications or even falsification of e-certificates. (2) The reputation of the open journal system is better with a sense of trust. This research uses library study method by implementing e-certificate in an open journal system with blockchain technology tools such as blockcerts. In order that the results of the e-certificate issuance go well and to avoid any crime that threatens the authenticity of the e-certificate, this blockchain is used to guarantee that the e-certificate is safe and not easily falsified, duplicated or even easily replaced by those not granted access rights. By using blockchain technology, the data collected will be well managed and not easily falsified.